Correction: A robust and flexible bulk superhydrophobic material from silicone rubber/silica gel prepared by thiol–ene photopolymerization. Issue 12 (11th March 2019) - Li, Yongsheng; Ren, Meng; Lv, Pengfei; Liu, Yingzhi; Shao, Hong; Wang, Cong; Tang, Changyu; Zhou, Yuanlin; Shuai, Maobing
Abstract : Correction for 'A robust and flexible bulk superhydrophobic material from silicone rubber/silica gel prepared by thiol–ene photopolymerization' by Yongsheng Li et al., J. Mater. Chem. A, 2019, DOI: ;10.1039/c8ta11111a .